ANALISIS RASIO KEUANGAN PADA PT. PLN (PERSERO) AREA PENYALURAN DAN PENGATUR BEBAN SISTEM SUL-SEL - Ibrahim Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
This study aims to determine the financial ratios on the PT. PLN (Persero) and the Regulatory Burden Area Distribution System Sulawesi Selatan for the years 2006-2010. This study uses secondary data in the form of corporate financial statements from 2006 to 2010. The results showed that: the analysis of liquidity ratio from the year 2006 - 2010 is known that the ability of the company PT. PLN (Persero) Distribution Area and Regulatory Burden-Sul System Cells in short-term debt has increased despite a decrease drasti in 2008. Lending rate indicated by the ratio laverage in recent years has decreased the impact on the company's activities so that a loss on the idea of 2009. Profitability is not so great especially in 2009 which led to declining investment losses as seen in Return on the investments.